“Analisis Pada Pekerja Yang Mengalami Pemutusan Hubungan Kerja Karena Kesalahan Berat” - Eka Saputra; Amanda Istianah Mutiawati (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
For employees and laborers in Indonesia, termination of employment is an inevitable fact, and laws regulating termination of employment are sought after in relation to the rights earned when termination happens. The worker's relationship with the employer may be terminated by the employer for reasons other than the worker's own actions or corporate decisions. For example, there are workers who are subject to termination because they committed an act of serious negligence and are still entitled to protection under the law. The issue at hand is how various termination-related legal laws have varying effects and how Law No. 11 of 2020 about Job Creation will modify the termination process and protection. The goal of this study is find out the laws and regulations governing termination and what are the legal instruments that support the rights of workers / workers affected by termination. This research uses exploratory qualitative methods using data through primary and secondary data sources. Based on the results of research, workers / workers get legal uncertainty regarding the rights obtained if they are terminated due to gross error.